DISTRIBUTION OF CALCIUM OXALATE CRISTAL, REDUCTION OF OXALATES, AND THE EFFECT OF CULTIVATION METHOD ON ITS FORMATION IN SOME VEGETABLES - Santoso, Agus Muji (Prodi Pendidikan Biologi FKIP UNS, 2013)
Oxalate is one of the plant metabolites. Oxalate can enter into the formation of both bio-soluble and insoluble oxalate in the some plants. Some plant which containing oxalates has been a good source of certain minerals, vitamins, dietary fiber, and some antioxidant phytochemicals. Most of vegetables are usually consumed both as a raw and or after cooking. On the other hand, oxalate can accumulate in the renal glomeroli and can lead to the formation of kidney stones and renal disorders. Besides that, the size, location, accumulation and formation oxalate acid to be calcium oxalate crystals in some vegetables may be affected by physical, chemical, and biological condition such us temperature, light exposure, pressure, time harvesting, pH, ion concentration, and macro and or micro ratio of field. This paper was aimed to describe: (1) distribution and formation of oxalate in some part of plants, (2) some methods how to reduce oxalates contents but still provided some good nutrition to healthy, (3) differences of the cultivation methods on oxalates content in some vegetables, in order to look for suitable cultivating method of vegetables. Key words: calcium oxalate, crystals, reduction, distribution, and formation